Effect of Silymarin on Gentamicin Induced Nephrotoxicity in Rats - Hilmi, Syeda Rubayat; Dewan, Zesmin Fauzia; Kabir, AKM Nurul; Islam, Muhammad Moinul; Yusuf, Md Abdullah; Afreen, Khandaker Nadia; Akter, Mahbuba (Bangladesh Journal of Infectious Diseases, 2023)
Background: As oxidative stress is an important factor in producing nephrotoxicity by a variety of drugs and chemicals; so, it may be assumed that agents having antioxidant property may protect the kidney from oxidative damage and can improve renal function. Objective: In the present study the ameliorative effect of silymarin was determined in a gentamicin-induced nephrotoxic model of rat. Methodology: This experimental animal study was carried out in the Department of Pharmacology at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2014 to January 2015 for a period of one year. In this study nephrotoxicity was induced by administering gentamicin (80 mg/kg/day for 7 days) intraperitoneally. Silymarin was administered (500 mg/kg/day for 14 days) orally concomitantly with gentamicin (7 days) and sacrificed on 15th day. To determine nephrotoxicity and amelioration of nephrotoxicity as well as the status of oxidative stress and lipid peroxidation; serum creatinine, serum urea, renal cortical reduced glutathione and malondialdehyde levels were estimated. Changes in renal architecture were estimated by histopathology of renal tissues. Results: Group (II) rats were injected gentamicin intraperitoneally for 7 days and sacrificed on 15th day showed significant (P< 0.001) increase of serum creatinine and urea level while there was significant (P< 0.001) reduction of renal cortical glutathione and increase (P< 0.001) in malondialdehyde concentration when compared to the control group (group I). This was supported by histological observations of H&E and PAS stained transverse section of renal cortex which suggested significant (P< 0.001) level of structural damage of renal cortex as evidenced from glomerular atrophy, tubular degeneration, presence of desquamated cellular debries and cast in the tubular lumen, mononuclear inflammatory cell infiltration. Statistically significant amelioration was observed in all the biochemical parameters which were supported by histology of renal cortex in silymarin treated group. Conclusion: The results from biochemical and histological observations of the present study indicate that silymarin was probably effective to ameliorate the signs of toxic damage to the renal cortex. Bangladesh Journal of Infectious Diseases, December 2023;10(2):71-76